2012
DOI: 10.1111/j.1365-2966.2012.22001.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hall effect in accretion flows

Abstract: Magnetic diffusion in accretion flows changes the structure and angular momentum of the accreting material. We present two power law similarity solutions for flattened accretion flows in the presence of magnetic diffusion: a secularly-evolving Keplerian disc and a magnetically-diluted free fall onto the central object. The influence of Hall diffusion on the solutions is evident even when this is small compared to ambipolar and Ohmic diffusion, as the surface density, accretion rate and angular momentum in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…They showed that the Hall effect promotes disc formation when the magnetic field is anti-aligned with the rotation axis, while it inhibits disc formation when the field and rotation axes are aligned, confirming earlier analytic studies (e.g. Braiding & Wardle 2012). Tsukamoto et al (2015a) performed non-ideal RMHD calculations that followed the collapse until just before stellar core formation that included both Ohmic resistivity and ambipolar diffusion (but not the Hall effect).…”
Section: Introductionsupporting
confidence: 62%
“…They showed that the Hall effect promotes disc formation when the magnetic field is anti-aligned with the rotation axis, while it inhibits disc formation when the field and rotation axes are aligned, confirming earlier analytic studies (e.g. Braiding & Wardle 2012). Tsukamoto et al (2015a) performed non-ideal RMHD calculations that followed the collapse until just before stellar core formation that included both Ohmic resistivity and ambipolar diffusion (but not the Hall effect).…”
Section: Introductionsupporting
confidence: 62%
“…If the interpretation of the counter rotation is correct, the effect of magnetic fields is a promising source to realize such a velocity structure. The physical mechanism to produce such a counter rotation through magnetic fields is known as the Hall effect, one of the non-ideal MHD effects (Wardle 2004;Wardle & Salmeron 2012;Braiding & Wardle 2012a;Braiding & Wardle 2012b). In collapsing cloud cores, the Hall effect induces toroidal (or azimuthal component of) magnetic fields from poloidal magnetic fields at the mid-plane of the pseudo-disk or the flattened envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Ambipolar diffusion and Ohmic resistivity lead to the diffusion of gas relative to the magnetic field and, therefore, are likely to lead to weaker fossil magnetic fields. The Hall effect is not diffusive but modifies the geometry of the magnetic field to increase or decrease the angular momentum in the dense gas that collapses to the equatorial plane (Braiding & Wardle 2012). Recent star formation studies have included some or all of these non-ideal effects (e.g.…”
Section: Introductionmentioning
confidence: 99%